2003
DOI: 10.1029/2001jb000989
|View full text |Cite
|
Sign up to set email alerts
|

Whole mantle P wave tomography using P and PP‐P data

Abstract: 1] We measured PP-P differential travel times on broadband seismograms of the Incorporated Research Institutions for Seismology (IRIS) network. The measurement was made by cross-correlating the observed PP waveform with the synthetic PP calculated from the observed P waveform. The effect of seawater reverberation on the measurement is taken into account if the PP bounce point is under ocean. The PP-P times measured after low-pass filtering is systematically shorter than those measured on raw broadband seismogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…Fukao et al (2004) found that their cross-sections beneath Hawaii between 400 and 800 km depth was anomalously hot (with anomalies of order 200-300 K at a lateral scale of 1,000 km), a feature which is consistent with the results from both seismic and EM inversions. The lack of quantitative agreement between (Fukao et al 2003). High-and low-velocity anomalies are colored blue and red, respectively, in linear scale.…”
Section: Global (And Semi-global) 3-d Inversions In Frequency Domainmentioning
confidence: 97%
“…Fukao et al (2004) found that their cross-sections beneath Hawaii between 400 and 800 km depth was anomalously hot (with anomalies of order 200-300 K at a lateral scale of 1,000 km), a feature which is consistent with the results from both seismic and EM inversions. The lack of quantitative agreement between (Fukao et al 2003). High-and low-velocity anomalies are colored blue and red, respectively, in linear scale.…”
Section: Global (And Semi-global) 3-d Inversions In Frequency Domainmentioning
confidence: 97%
“…High‐velocity anomalies extending to depths around 200 km are associated with the lithosphere of East Antarctica. Global P wave velocity tomography studies derived from travel times of P and PP waves have provided images beneath the region, but this resolution is poor because of the sparse station distribution and lack of seismicity in Antarctica [e.g., Fukao et al , 2003]. Global tomography derived from travel times of S waves has the same problem.…”
Section: Introductionmentioning
confidence: 99%
“…We used the travel times measured at PLUME and BBOBS stations together with the ISC P-wave arrival time data for global mantle raytheoretical tomography (e.g., Fukao et al, 2003). The spatial resolution achieved by our calculations in the lower mantle is estimated to be ~500 km.…”
Section: Fig 5 Bbobs (Large Solid Triangles) and Plume (Open Triangmentioning
confidence: 99%